Hierarchy, Symmetry and Scale in Mathematics and Bi-Logic in Psychoanalysis, with Consequences. (14th April 2021) - Murtagh, Fionn
Abstract : Hierarchy has properties of symmetry and scale. All that is related to hierarchy provides important perspectives on many other domains. The primary focus here is on renowned psychoanalyst Ignacio Matte Blanco's Bi-Logic. Bi-Logic relates to the two modes of being, respectively symmetry and asymmetry in thought and reasoning and brain processes, in unconscious and in conscious modes of being. Some further consequences and implications are noted. These include relevance and potential in social sciences; in qualitative as well as quantitative literary analysis, and content analytics of text, speech, visual recording, and so on; in security and forensics; and in the contemporary theme of research and development relating to Big Data analytics.